Advanced biomaterials and their potential applications in the treatment of periodontal disease. (3rd July 2016) - Chen, Xi; Wu, Guofeng; Feng, Zhihong; Dong, Yan; Zhou, Wei; Li, Bei; Bai, Shizhu; Zhao, Yimin
Abstract: Periodontal disease is considered as a widespread infectious disease and the most common cause of tooth loss in adults. Attempts for developing periodontal disease treatment strategies, including drug delivery and regeneration approaches, provide a useful experimental model for the evaluation of future periodontal therapies. Recently, emerging advanced biomaterials including hydrogels, films, micro/nanofibers and particles, hold great potential to be utilized as cell/drug carriers for local drug delivery and biomimetic scaffolds for future regeneration therapies. In this review, first, we describe the pathogenesis of periodontal disease, including plaque formation, immune response and inflammatory reactions caused by bacteria. Second, periodontal therapy and an overview of current biomaterials in periodontal regenerative medicine have been discussed. Third, the roles of state-of-the-art biomaterials, including hydrogels, films, micro/nanofibers and micro/nanoparticles, developed for periodontal disease treatment and periodontal tissue regeneration, and their fabrication methods, have been presented. Finally, biological properties, including biocompatibility, biodegradability and immunogenicity of the biomaterials, together with their current applications strategies are given. Conclusive remarks and future perspectives for such advanced biomaterials are discussed.